2022
DOI: 10.3389/fmicb.2022.996753
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiological characteristics an outbreak of ST11 multidrug-resistant and hypervirulent Klebsiella pneumoniae in Anhui, China

Abstract: Klebsiella pneumoniae has become a primary threat to global health because of its virulence and resistance. In 2015, China reported multidrug-resistant (MDR) and hypervirulent K. pneumoniae (hvKp) isolates. The emergence of MDR-hvKp poses a significant threat to public health. We collected 76 MDR K. pneumoniae isolates from the same hospital, of which there were a total of six MDR-hvKp isolates. We performed multilocus sequence typing (MLST) and capsular typing, whole genome sequencing, comparative genome anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Similarly, to detect SNPs in 22091569, it was compared with ST307 isolates ( He et al, 2022 ). Here, we identified 17 mutations were same in each ST307 isolates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, to detect SNPs in 22091569, it was compared with ST307 isolates ( He et al, 2022 ). Here, we identified 17 mutations were same in each ST307 isolates.…”
Section: Resultsmentioning
confidence: 99%
“…Antibiotic susceptibility of all clinical isolates was determined by previously described methods with slight modifications ( He et al, 2022 ). The MICs of routinely used antibiotics ( Supplementary Table S2 ), were determined by the VITEK 2 Compact System and the results of the antimicrobial susceptibility tests were interpreted according to the Clinical Laboratory Standards Institute ( CLSI, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ST11 is a single-locus variant (tonB) of ST258, and both them belong to the clone complex CC258 [ 15 ]. ST258 is prevalent in the United States and several European countries[ 34 ], while ST11 is the most common type in Asia, and accounts for up to 60% of CRKP in China [ 35 , 36 ]. In addition, we found that NDM-1-producing CRKP ST17 isolates had an outbreak in our hospital, and the isolates mainly came from neonatology department.…”
Section: Discussionmentioning
confidence: 99%
“…[8]; [9]; [10]; [11]. MDR hypervirulent K. pneumoniae (hvKp) strains have been emerging, spawning a new generation of hypervirulent "superbugs" [12]. Newer therapeutics, such as vaccines or monoclonal antibodies, are needed to combat MDR K. pneumoniae.…”
Section: Introductionmentioning
confidence: 99%